2021
DOI: 10.4102/sajhrm.v19i0.1509
|View full text |Cite
|
Sign up to set email alerts
|

The development of an organisational effectiveness model

Abstract: The research aims to build and validate a conceptual model of relationships between perceived leadership attributes (PLAs), social capital (SC) and organisational effectiveness (OE).Motivation for the study: State-owned companies (SOCs) in South Africa are under enormous pressure and plagued by issues such as mismanagement, poor leadership and poor service delivery. Central to these issues is the relationship between leadership and its stakeholders, and how it affects OE. There is lack of theory about the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Similar studies suggested that there was a statistically significant positive relationship between leadership and planning and decision-making (Menazel, Muhammad, Ebrahim, & Anan, 2015). Leaders courage, trust and reputation received the highest level of consensus helps to validate leaders accountability (Titus & Hoole, 2021). Leadership by example and high communication leadership influence human resource management directly and positively (Gallego-Nicholls, Pagán, Sánchez-García, & Guijarro-García, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies suggested that there was a statistically significant positive relationship between leadership and planning and decision-making (Menazel, Muhammad, Ebrahim, & Anan, 2015). Leaders courage, trust and reputation received the highest level of consensus helps to validate leaders accountability (Titus & Hoole, 2021). Leadership by example and high communication leadership influence human resource management directly and positively (Gallego-Nicholls, Pagán, Sánchez-García, & Guijarro-García, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Organizations and companies will gain competitive advantage by involving in good corporate citizenship activities like doing corporate social responsibility (CSR) work because such selflessness values are increasingly becoming intangible assets much sought after in human and intellectual capital within the modern competitive worlds (Titus & Hoole, 2021). Similarly, universities as a multi-functional organization should develop social responsibility initiatives just like other organizations as an approach to meet the stakeholders' expectation and satisfaction (Vasilescu, Barna, Epure, & Baicu, 2010).…”
Section: Introductionmentioning
confidence: 99%